Ethical Considerations in AI-Powered Work Environments: A Literature Review and Theoretical Framework for Ensuring Human Dignity and Fairness - Oyekunle, David; Boohene, David; Preston, David (International Journal of Scientific Research and Management (IJSRM), 2024)
This article critically examines the integration of artificial intelligence (AI) into work environments, focusing on the ethical implications that arise. It seeks to underscore the need for balancing technological advancements with the protection of human dignity and fairness, exploring how AI's transformative potential can be harmonized with the core tenets of human rights.The article utilizes a comprehensive literature review to construct a theoretical framework that outlines AI's capabilities and ethical considerations. This framework encompasses the interdisciplinary foundations of AI, including its roots in cognitive psychology, decision theory, and computer engineering. It further delves into the ethical dilemmas presented by AI in the workplace, such as privacy concerns, the risk of bias, issues of accountability, and the broader impact on human rights. This exploration is aimed at understanding the complexities of AI's integration into the labor market and its implications for occupational safety and health.The findings of the article highlight the dual nature of AI as both a catalyst for efficiency and innovation and a source of ethical challenge. It's important to include a lot of different points of view and include everyone in the process of developing AI to make it more fair and respect human rights. Laws and policies need to keep changing to keep up with AI's progress and protect people legally from possible abuses. Strong moral guidelines and clear AI systems are also needed to protect privacy and reduce bias.The study's originality and value emphasize the need for AI ethical discussions in human rights contexts, contribute to technology governance and human rights discussions, and discuss theoretical debates on human dignity, fairness, and privacy in the face of technological advancement.